Exploring the Role of Knowledge Sharing and Innovative Behavior in Shaping Shared Leadership among Student Organizations - Simamora, Debora Jeswita; Mariana, Ana (Lentera Ilmu Nusantara, 2025)
This study aims to analyze the influence of knowledge sharing and innovative behavior on shared leadership in the Student Association of the Faculty of Intelligent Technology and Engineering. In today's collaborative era, leadership practices are no longer centralized, but rather distributed collectively based on contributions and trust between members. This study uses a causal quantitative approach with primary data obtained by distributing questionnaires to 90 respondents, all of whom are active members of the organization. The number of respondents reflects the entire population of the organization, thereby ensuring comprehensive coverage of perspectives. The sampling technique used was saturated sampling, and the data were analyzed using multiple linear regression with the help of SPSS software. The results showed that knowledge sharing has a significant influence on the formation of shared leadership, because the process of sharing knowledge encourages collaboration and recognition of the competence of each member. In addition, innovative behavior also has a significant influence, where individuals who show creativity and initiative tend to be trusted to lead situationally. These findings confirm that an organizational environment that is open to the exchange of knowledge and innovative ideas will support the formation of adaptive and participatory collective leadership patterns.